Project Achieving Method of Subsection Modulation Technique Applied on Diesel Locomotive Converter - YU Hua; LI Yan; LI Guofeng; ZHAN Zhejun (机车电传动)
Due to the direct relation between switching losses and operation frequency of locomotive converter, proper modulation modes should be used to meet the requirement of different frequency sections. Based on asynchronous modulation, synchronous modulation and single pulse modulation, a project achieving method with DSP was provided. Simulation and experiments proved the validity of the method.